Synthesis, characterization and biological studies of a new adduct single crystal of hexamethylenetetramine:benzilic acid. (2020) - Siva, G.; Bharathikannan, R.; Mohanbabu, B.
Graphical abstract: A new adduct hexamethylenetetramine benzilic acid (HMTBA) was synthesized and characterized by various physico-chemical and spectral techniques. In addition, X-ray analysis was carried out in order to scrutinize the crystal structure of the resulted adduct compound. The HMTBA adduct exhibited noticeable growth inhibition against fungal and bacterial species. The antioxidant activity of the HMTBA adduct with DPPH was investigated by electronic absorption spectroscopy which indicated that the compound was significant scavenging activity. Abstract: The novel hexamethylenetetramine benzilic acid (HMTBA) adduct single crystal was synthesized by slow evaporation solution growth technique. The HMTBA crystal was confirmed by single crystal XRD and Further, the structure was investigated by various spectroscopic techniques such as FT-IR, UV–Vis, 1 H, 13 C NMR, Powder XRD spectroscopy and Z-scan studies. Thermal properties of the HMTBA was studied by using thermo-gravimetric analysis (TGA) and it was stable up to 187.6 °C. In addition, the newly synthesized HMTBA adduct was studied for biological application.